Design of ergonomic chair for grinding operation - Andrean Emaputra; Taufik Hidayat; Gunawan Budi Susilo (Jurnal Teknosains, 2020)
One of essential production activities is grinding process. This process mainly involves the constant activity of eroding a surface to be smoother or more evenly, cutting a workpiece, creating profiles like angles and arches, sharpening a cutting tool, and finishing a final product. Meanwhile, there is no study evaluating the risk levels of workers working on grinding, and there is no unique chair specifically designed for the process. Therefore, this study aims to assess the risk levels of a grinding worker and to propose the design of an ergonomic chair that is adjustable, comfortable, durable, and keen to be used. The risk levels of the grinding workers were evaluated using REBA, while the ergonomic chair design was based on anthropometric data taken from 4 grinding workers in Bantul, Special Region of Yogyakarta, Indonesia. The researchers selected a buttock-popliteal length (seat depth), lower leg length (popliteal height) and hip breadth sitting as anthropometric measures to make a chair design for the grinding operations. After that, the existing adjustable chair designs were also considered and evaluated to get better adjustableergonomic chair design for the grinding operations. The results show that it is important that the stakeholders improve most of the grinding operations of the workers, especially by using an ergonomic chair design for grinding operation that is adjustable, comfortable, durable, and reliable. The chair height can be adjusted from 361-414 mm to adapt with the users, and the variation in product height aims to prevent bending on the back. Finally, the grinding chair can reduce the risk level from the high and medium level to the low-risk levels of working postures.